2023
DOI: 10.1371/journal.pclm.0000207
|View full text |Cite
|
Sign up to set email alerts
|

Identifying key-psychological factors influencing the acceptance of yet emerging technologies–A multi-method-approach to inform climate policy

Julius Fenn,
Jessica F. Helm,
Philipp Höfele
et al.

Abstract: The best combination of possible climate policy options (mitigation, adaptation and different climate engineering technologies) to tackle climate change is unknown. Climate policy is facing a hard decision in answering the question whether climate engineering technologies should be researched, limitedly deployed or even deployed at global scale. Such technologies bear large epistemic and ethical uncertainties and their use as well as non-use might have severe consequences. To deal with such uncertainties, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“… 2020 , Fenn et al . 2023 ). However, and thirdly, factors are identified that may increase support for SAI: the perceived urgency and seriousness of climate change (Corner and Pidgeon 2015 , Merk et al .…”
Section: Current Research: Risks Publics and Media Coveragementioning
confidence: 99%
See 1 more Smart Citation
“… 2020 , Fenn et al . 2023 ). However, and thirdly, factors are identified that may increase support for SAI: the perceived urgency and seriousness of climate change (Corner and Pidgeon 2015 , Merk et al .…”
Section: Current Research: Risks Publics and Media Coveragementioning
confidence: 99%
“… 2018 , Jobin and Siegrist 2020 , Fenn et al . 2023 ); and viewing science and technology as a solution for climate change (Mercer et al . 2011 ).…”
Section: Current Research: Risks Publics and Media Coveragementioning
confidence: 99%